Pre- and Post-Antibiotic Epoch: Rethinking Antimicrobial Resistance - Tanaka, Aiko Misaki (Science Insights, 2026)
The global escalation of antimicrobial resistance (AMR) has transformed medicine into a precarious endeavor, challenging the foundational trust in antibiotics that has defined modern healthcare. The pre-antibiotic epoch was characterized by high morbidity and mortality from infections, where even minor injuries could become lethal. The post-antibiotic epoch, paradoxically, is emerging not from the absence of antibiotics but from their misuse, overprescription, and the consequent selection pressure that drives resistant pathogens. This transitional era compels a reevaluation of how societies, healthcare systems, and scientific research address infectious diseases. While antibiotic discovery slowed decades ago, resistance mechanisms proliferated, creating a silent but potent threat. Rethinking AMR requires more than novel drug development—it demands a paradigm shift in stewardship, diagnostics, public awareness, and global cooperation. This article argues that acknowledging the lessons of the pre-antibiotic era, understanding the vulnerabilities of our post-antibiotic present, and proactively reshaping clinical and societal behaviors are essential to preserving effective antimicrobial therapy for future generations.